2018
DOI: 10.1371/journal.pone.0192992
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the intestinal microbiota between uninfected piglets and piglets infected with porcine epidemic diarrhea virus

Abstract: Porcine epidemic diarrhea, a disastrous gastrointestinal disease, causes great financial losses due to its high infectivity, morbidity and mortality in suckling piglets despite the development and application of various vaccines. In this study, high-throughput sequencing was used to explore differences in the intestinal microbiota between uninfected piglets and piglets infected with porcine epidemic diarrhea virus (PEDV). The results revealed that the small intestinal microbiota of suckling piglets infected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 35 publications
5
34
0
Order By: Relevance
“…This sensitivity may generate individual differences in microorganisms, even in piglets from the same cohort [35]. Here, we found that PEDV infection significantly altered the gut microbiota in piglets, an outcome that was confirmed in several other studies [20][21][22][23].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This sensitivity may generate individual differences in microorganisms, even in piglets from the same cohort [35]. Here, we found that PEDV infection significantly altered the gut microbiota in piglets, an outcome that was confirmed in several other studies [20][21][22][23].…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, previous research has shown that the proportions of Escherichia-Shigella, Enterococcus, Fusobacterium, and Veillonella increased significantly in PEDV-infected piglets, while those of short-chain fatty acid (SCFA)-producing bacteria (e.g., Rikenellaceae_RC9_gut_group, Butyricimonas, and Alistipes) underwent a decrease [21]. Moreover, the gut microbiota of PEDV-infected piglets was shown to exhibit significant changes at the genus and phylum levels [22] that are likely to disrupt microecological homeostasis.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In pigs, several studies have reported that there exists a close relationship between diarrhea-relating coronaviruses and intestinal microbiota (Huang et al, 2018;Liu et al, 2015;Song et al, 2017;Tan et al, 2019). It has been reported that PEDV infection induced gut microbial dysbiosis, leading to a reduction in beneficial bacteria and an increase in pathogenic bacteria.…”
mentioning
confidence: 99%